“It was the first time Pablo sang in a choir…” Reflections on Good Diction as the Imposition of a Eurocentric Aesthetic Canon (Orfeu, 2025)
This study analyzes the influence of the Eurocentric phonetic-aesthetic canon on Latin American choral singing and examines how the imposition of a “correct” pronunciation affects performers’ identity and expression. Drawing on a specific case from a choral rehearsal that illustrates a broader trend, it shows how certain standards of European classical singing homogenize Spanish diction, thereby relegating the richness of its regional linguistic variations and distancing Spanish-speaking audiences from a performance perceived as unfamiliar and foreignized. From a decolonial perspective, the notion of “proper diction” is challenged, and concepts such as aisthesis—understood here as aesthetic perception shaped by sociocultural context—and sound symbolism—the relationship between sound and meaning in linguistic expression—, are proposed as tools to enhance expressive authenticity in choral singing. This study advocates for a more inclusive approach that acknowledges the inherent musicality of Spanish and its varieties, which not only promotes a more genuine and representative interpretation of Latin American cultural diversity, but also fosters a deeper connection between performers and audiences through the recognition of sonic identity.
Keywords: Spanish singing; good diction; Eurocentric aesthetic canon; decolonial alternative